Does Mindfulness Enhance Critical Thinking? Evidence for the Mediating Effects of Executive Functioning in the Relationship between Mindfulness and Critical Thinking - Noone, Chris; Bunting, Brendan; Hogan, Michael J. (Frontiers in Psychology, 2016)
Mindfulness originated in the Buddhist tradition as a way of cultivating clarity of thought. Despite the fact that this behaviour is best captured using critical thinking assessments, no studies have examined the effects of mindfulness on critical thinking or the mechanisms underlying any such possible relationship. Even so, mindfulness has been suggested as being beneficial for critical thinking in higher education. Critical thinking is recognised as an important higher-order cognitive process which involves the ability to analyse and evaluate evidence and arguments. Such non-automatic, reflective responses generally require the engagement of executive functioning which includes updating, inhibition and shifting of representations in working memory. Based on research showing that mindfulness enhances aspects of executive functioning and certain higher-order cognitive processes, we hypothesised that individuals higher in facets of dispositional mindfulness would demonstrate greater critical thinking performance, and that this relationship would be mediated by executive functioning. Cross-sectional assessment of these constructs in a sample of 178 university students was achieved using the observing and non-reactivity sub-scales of the Five Factor Mindfulness Questionnaire, a battery of executive functioning tasks and the Halpern Critical Thinking Assessment. Our hypotheses were tested by constructing a multiple meditation model which was analysed using Structural Equation Modelling. Evidence was found for inhibition mediating the relationships between both observing and non-reactivity and critical thinking in different ways. Indirect-only (or full) mediation was demonstrated for the relationship between observing, inhibition and critical thinking. Competitive mediation was demonstrated for the relationship between non-reactivity, inhibition and critical thinking. This suggests additional mediators of the relationship between non-reactivity and critical thinking which are not accounted for in this model and have a negative effect on critical thinking in addition to the positive effect mediated by inhibition. These findings are discussed in the context of the Default Interventionist Dual Process Theory of Higher-order Cognition and previous studies on mindfulness, self-regulation, executive function and higher-order cognition. In summary, dispositional mindfulness appears to facilitate critical thinking performance and this effect is mediated by the inhibition component of executive functioning. However, this relationship is not straightforward which suggests many possibilities for future research.